Improvement of the wire compensation configuration model for improving part accuracy in cylindrical wire electrical discharge turning. (17th January 2020) - Izamshah, R.; Akmal, M.; Kasim, M. Shahir
Demand for complex micro-sized shape components has driven the industries on the development of a new machine and fabrication technique. One of the latest techniques is by combining a sparking electrode wire with a rotating workpiece, known as cylindrical wire electrical discharge turning (CWEDT). However, owing to the uncontrolled discharge energy, the existence of dynamic run-out and valid wire positioning compensation estimations in the CWEDT process affect its capability of producing micro-sized components. This paper proposes a new compensation configuration model for the CWEDT process that aims to improve the dimensional accuracy. The developed configuration model emphasises the way to obtain the desired diameter that can be used as the input value for positioning the electrode wire through a machine system. Sets of experimental runs were performed to confirm its validity. Analytical results show that the developed model has improved the part accuracy up to 95% and is capable of eliminating overcut error, hence, verifying its validity.